The role of IGF2BP3/SPOP/c-Myc loop in paclitaxel resistance of endometrial cancer - Yidong Ge; Lili Kong; Yuxuan Li; Zongdong Yu; Fengguang Zhai; Ziqing Zhan; Gun Chen; Shuyan Wang; Haoyun Wang; Yuxuan Wang; Jianan Zhao; Lechen Hu; et al. (Communications Biology)
Abstract Paclitaxel combination therapy is the main chemotherapy regimen for endometrial cancer (EC); however, subsequent drug resistance is a bottleneck limiting its widespread clinical application. We found that human insulin-like growth factor 2 mRNA-binding protein 3 (IGF2BP3) was abnormally elevated in paclitaxel-resistant EC cells and confirmed that the reduction of IGF2BP3 can effectively improve the sensitivity of EC cells to paclitaxel in vitro and in vivo. Mechanistically, elevated IGF2BP3 promotes the half-life of c-Myc by competitively inhibiting Speckle-type POZ protein (SPOP)-mediated ubiquitination and degradation of c-Myc. As a transcription factor, c-Myc can bind to the promoter of IGF2BP3, thus contributing to the increased transcription of IGF2BP3 via positive feedback and forming a signaling loop that ultimately causes the accumulation of c-Myc-induced paclitaxel resistance. Based on these findings, the application of c-Myc inhibitors (10058-F4) combined with paclitaxel helped paclitaxel-resistant EC cells regain paclitaxel sensitivity in vitro and in vivo. Together, we reveal the underlying mechanism of paclitaxel resistance in endometrial cancer cells and provide insights into treatment strategies for paclitaxel-resistant EC patients.